CPEB3 is associated with human episodic memory - Vogler, Christian; Spalek, Klara; Aerni, Amanda; Demougin, Philippe; Müller, Ariane; Huynh, Kim-Dung; Papassotiropoul, Andreas; De Quervain, Dominique J. (Frontiers in Behavioral Neuroscience, 2009)
Cytoplasmic polyadenylation element-binding (CPEB) proteins are crucial for synaptic plasticity and memory in model organisms. A highly conserved, mammalian-specific short intronic sequence within CPEB3 has been identified as a ribozyme with self-cleavage properties. In humans the ribozyme sequence is polymorphic and harbors a single nucleotide polymorphism which influences cleavage activity of the ribozyme. Here we show that this variation is related to performance in an episodic memory task and that the effect of the variation depends on the emotional valence of the presented material. Our data support a role for human CPEB3 in human episodic memory.